Range of motion and injury occurrence in elite spanish soccer academies. Not only a hamstring shortening—related problem - Sanz, A.; Pablos, C.; Ballester, R.; Sánchez-Alarcos, J. V.; Huertas, F. (The Journal of Strength and Conditioning Research, 2020)
Age-related development of range of motion (ROM) during an active hip flexion (active straight leg raise) and its relationship with hamstring injury occurrence were examined in 1657 young male soccer players (9-18 years of age). Age-related differences in ROM showed a significant decrease from U9 to U11 (p = 0.001), from U11 to U13 (p < 0.005), and from U9 to U13 (p < 0.001), whereas ROM increased from U13 to U15 and from U13 to U18 (both p's < 0.001). Interestingly, younger and older players reached similar ROM values (U9-U18, p = 0.87). Higher ROM was found in dominant than nondominant leg in all age groups (all ps < 0.001). No differences related to playing position were found on ROM (all ps > 0.478). During the follow-up period (11 months) 97 hamstring injuries were reported showing higher rates in the older age groups (p < 0.001) and outfield players (p < 0.001). Remarkably, no differences in ROM average were found between injured players and noninjured players (p = 0.152). Our results suggest that ROM during hip flexion does not only depend on the hamstrings shortening but also on the variables related to joint stability, motor control, and hip flexor muscle weakness. Sport scientists in youth sport soccer academies should develop age-specific screening and action plans to develop strength, motor control, and flexibility to optimize ROM and reduce injuries from the grassroots stages.